Rhodiola rosea Exerts Antiviral Activity in Athletes Following a Competitive Marathon Race - Ahmed, Maryam; Henson, Dru A.; Sanderson, Matthew C.; Nieman, David C.; Zubeldia, Jose M.; Shanely, R. Andrew (Frontiers in Nutrition, 2015)
Rhodiola rosea, a medicinal plant with demonstrated adaptogenic properties, has recently been reported to contain active compounds with antimicrobial activity. The goal of this study was to measure the antiviral and antibacterial properties of the bioactive metabolites of Rhodiola rosea in the serum of experienced marathon runners following supplementation. Marathon runners, randomly divided into two groups, ingested 600 mg/day of Rhodiola rosea (n = 24, 6 female, 18 male) or placebo (n = 24, 7 females, 17 males) for 30 days prior to, the day of, and 7 days post-marathon. Blood serum samples were collected the day before, 15 min post-, and 1.5 h post-marathon. Serum from Rhodiola rosea-supplemented runners collected after marathon running did not attenuate the marathon-induced susceptibility of HeLa cells to killing by vesicular stomatitis virus. However, the use of Rhodiola rosea induced antiviral activity at early times post-infection by delaying an exercise-dependent increase in virus replication (P = 0.013 compared to placebo). Serum from both groups collected 15 min post-marathon significantly promoted the growth of Escherichia coli in culture as compared to serum collected the day before the marathon (P = 0.003, all subjects). Furthermore, the serum from subjects ingesting Rhodiola rosea did not display antibacterial properties at any time point as indicated by a lack of group differences immediately (P = 0.785) or 1.5 h (P = 0.633) post-marathon. These results indicate that bioactive compounds in the serum of subjects ingesting Rhodiola rosea may exert protective effects against virus replication following intense and prolonged exercise by inducing antiviral activity.